Around two false equations: good cocaine, good cocaine; bad cocaine bad cocaine - Romano, Ruggiero (1982)
The discovery and conquest of America was not only an armed clash, a meeting of men, a confrontation of cultures and civilizations, but also an exchange of plants and animals: throughout the sixteenth century (the process, moreover, will continue until today) in the Atlantic Ocean diametrically opposite paths cross that take the bull or the wheat... to America and the turkey and the corn to Europe. The "discovery" was also largely the observation of a flora and fauna that were different in the eyes of the "discoverers".